Inhibition of human α-amylase by dietary polyphenols. (December 2015) - Nyambe-Silavwe, Hilda; Villa-Rodriguez, Jose A.; Ifie, Idolo; Holmes, Melvin; Aydin, Ebru; Jensen, Jane Møller; Williamson, Gary
Highlights: Remarkable variation reported in inhibition constants for polyphenols on α-amylase. We present an optimised assay for measuring inhibition of α-amylase. Optimisation includes the removal of certain polyphenols during the assay. EGCG and acarbose are potent inhibitors. Amylose and amylopectin are preferred and natural substrates for the assay. Abstract: Functional foods offer the possibility to modulate the absorption of sugars, leading to benefits for diabetics and those with metabolic syndrome. As part of the characterisation of such foods, inhibition of α-amylase is used to assess components for their potential ability to modify the post-prandial glycaemic response. Many publications on phenolics as potential inhibitors report widely varying assay conditions leading to variable estimates of inhibition. On this basis, we have optimised the in vitro α-amylase inhibition assay and, in particular, we show the importance of removing certain polyphenols after the enzymic reaction when using 3, 5-dinitrosalicylic acid since they interfere with this reagent. There was a substantial 5-fold effect on acarbose IC50 values when working just outside optimal conditions. This shows that inappropriate assay conditions, such as excess enzyme, greatly influence IC50 values and could explain some discrepancies in the existing literature.